Photocatalytic overall water splitting by graphitic carbon nitride. Issue 9 (26th June 2021) - Niu, Ping; Dai, Junjing; Zhi, Xiaojuan; Xia, Zhonghui; Wang, Shulan; Li, Li
Abstract: Photocatalytic overall water splitting (OWS) without using any sacrificial reagent to realize H2 and O2 production in the stoichiometric ratio of 2:1 is viewed as the "holy grail" in the field of solar fuel production. Developing stable, low cost, and nontoxic photocatalysts that have satisfactory solar‐to‐hydrogen conversion efficiency is of significance but challenging for realizing the large‐scale use of this sustainable technology. Among various photocatalysts, graphitic carbon nitride (GCN) has shown great potential as an ideal candidate to fulfill the breakthrough in this dynamic research field due to its attractive physicochemical properties. Herein, for the first time, the state‐of‐the‐art research progress of GCN for photocatalytic OWS is reviewed. We first summarize the basic principle of photocatalytic OWS along with the advantages/challenges of GCN introduced. The strategies that have been used to modulate the OWS activity of GCN are then reviewed, including cocatalyst investigation, morphology modulation, atomic structure modification, crystallinity engineering, and heterostructure construction. Toward the end of the review, the concluding remarks and perspectives for the future development are presented, with our expectation to provide some new ideas for the design of advanced OWS photocatalysts. Abstract : Developing proper photocatalysts for overall water splitting is of great significance for the sustainable and clean energy production. The research progress of photocatalytic overall water splitting by graphitic carbon nitride with the focus on its developed modulation strategies is systematically reviewed in this work, which aims to provide some strategies and in‐depth understanding for the design of high performance photocatalysts for overall water splitting.